A simple method for landslide risk assessment in the Rivière Aux Vases basin, Quebec, Canada. (December 2022) - Regmi, Amar Deep; Agrawal, Nirupama
Abstract: This research offers a simple approach for landslide risk assessment on a basin-scale in the Quebec Province of Canada, where landslides are common. Landslide inventory and distribution mapping are developed for the Aux Vases Watershed, the most landslide-affected area in the Saguenay region, for a detailed landslide hazard and risk assessment process. The study uses publicly available data from Google Earth images, published literature, Government data sources for topographic maps and landuse information, as well as the 2016 Census Profile of the Saguenay region of Quebec. ArcGIS software is used for spatial data processing and analyzing datasets to develop maps of landslide susceptibility, vulnerability, and lack of coping capacity, and a landslide risk map of the Aux Vases Watershed was developed. Landslide risk assessment is critical for minimizing the loss of life and property from potential landslides in the study area and empowers communities with useful information so they can make informed decisions to mitigate the risk and build coping capacities. In addition, risk reduction policies and strategies, public safety, and future development planning initiatives will benefit from this research. Highlights: Spatial landslide risk assessment in Saguenay region of Quebec, Canada. Accounts for institutional coping capacities to gauge community resiliency. Enables communities to better understand risks and engage in mitigation. Promotes adaptation strategies in at-risk communities. A useful tool for governments to prioritize risks and resource allocation.